Studi Komperatif Sistem Hukum Wakaf Antara Negara Indonesia dan Malaysia - Islamiyati (Asosiasi Pengajar dan Peneliti Hukum Ekonomi Islam Indonesia (APPHEISI), 2019)
Indonesia and Malaysia are developing countries, with the form of waqf law, they have similarities and differences, from its implementation, legal basis, system, as well as to the settlement of waqf disputes. This study analyzes the similarities and differences between the Indonesian and Malaysian state waqf legal systems. The benefit is in the expansion of the waqf legal discourse at the international level. This type of research is a literature that uses a normative juridical approach, the type of data is secondary data consisting of primary, secondary and tertiary legal materials, the data analysis method is comparative study. The results of the study explain that the implementation of waqf law between Indonesia and Malaysia, which has their respective characteristics, is adjusted to the typology of the community. The form of Indonesia and Malaysia is different, of course the legal system is also different. The point of similarity between these two countries is that the Islamic legal framework with the Shafi'i school of thought is not absolute. However, in Malaysia it only applies in certain states. Keywords : Comparative, legal system, waqf, Malaysia, Indonesia. Abstrak Indonesia dan Malaysia, merupakan negara berkembang, kaitannya dengan hukum wakaf memiliki persamaan dan perbedaan, dari pelaksanaannya, dasar hukumnya, sistemnya, maupun pada penyelesaian sengketa wakaf. Penelitian ini menganalisis tentang persamaan dan perbedaan antara sistem hukum wakaf negara Indonesia dan Malaysia. Manfaatnya pada perluasan wacana hukum wakaf di tingkat International. Jenis penelitian adalah kepustakaan yang menggunakan pendekatan yuridis normatif, jenis datanya yakni data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier, metode analisis datanya comperative study. Hasil penelitian menjelaskan bahwa pelaksanaan hukum wakaf antara negara Indonesia dengan Malaysia, mempunyai ciri khas masing-masing yang disesuaikan dengan tipologi masyarakatnya. Bentuk negara Indonesia dan Malaysia berbeda, tentunya sistem hukumnya juga berbeda. Titik persamaan kedua negara ini adalah pada kerangka hukum Islam yang bermazhab Syafi’i tidak mutlak. Namun, di Malaysia hanya berlaku di negara bagian tertentu saja. Kata Kunci : Komperatif, sistem hukum, wakaf, Malaysia, Indonesia.